Composition control and preparation method of high-strength and tough isotropic additively manufactured 316L stainless steel
By optimizing the alloy composition and printing parameters of 316L stainless steel, adjusting the content of elements such as Cr, Mo, Si, and changing the solidification path, the conversion from columnar crystal to isometric crystal in additive manufacturing stainless steel materials is achieved, solving the anisotropy problem caused by columnar crystals in additive manufacturing process, and improving the mechanical properties of the material and the uniformity of the microstructure.
Patent Information
- Application Number
- CN202410469970.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-18
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-04-18
AI Technical Summary
During the additive manufacturing process, a large number of columnar crystals and texture phenomena were observed in the sample parallel to the printing direction, resulting in anisotropy of performance and cracking sensitivity of the alloy.
By optimizing the alloy composition and printing parameters of 316L stainless steel, adjusting the content of elements such as Cr, Mo, Si, etc., changing the solidification path, changing from the primary austenite mode to the primary ferrite mode, controlling the grain size and morphology, and realizing the transformation from columnar crystal to isometric crystal.
The conversion from columnar crystal to equiaxed crystal in additively manufactured stainless steel materials is realized, and the grains of alloy are refined, which improves the mechanical properties of the material and the uniformity of the microstructure, and reduces the anisotropy of the performance.
Smart Images

Figure CN118341987B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of additive manufacturing core materials, and in particular relates to a composition design and preparation strategy for additive manufacturing stainless steel to refine grains and eliminate anisotropy. Background Art
[0002] Additive manufacturing technology is a preparation method that controls the printing of alloys layer by layer through computer programs, and can provide extremely high degrees of freedom in the manufacturing process to produce parts of various complex geometries. Therefore, additive manufacturing is leading multiple industries such as aerospace, automobiles, biomedicine, and energy into a new era of manufacturing. Compared with traditional manufacturing technology, additive manufacturing technology can greatly shorten the production cycle and reduce material costs. In addition, the alloys obtained by additive manufacturing technology undergo rapid solidification and repeated heating during the preparation process, and their unique microstructure provides new ideas for solving the problem of strong and tough coordination.
[0003] However, during the rapid cooling process of additive manufacturing, a large number of columnar crystals and texture phenomena were observed in the samples parallel to the printing direction. The appearance of columnar crystals will lead to anisotropy of properties and increase the cracking sensitivity of the alloy. Therefore, the formation of columnar crystals has become an urgent problem to be solved in the process of industrialization of additive manufacturing alloys.
[0004] Common methods to achieve grain refinement or equiaxed crystal structure in additive manufacturing alloys include adjusting process parameters and scanning strategies, adding inoculants to produce a large number of heterogeneous nucleation sites, or adjusting the chemical composition of additive manufacturing alloys to change the solidification path.
[0005] Although the growth of columnar grains can be prevented by printing process parameters or scanning strategies, the efficiency of grain refinement is low. In addition, although the addition of inoculants can obtain suitable microstructures and excellent mechanical properties, it is difficult to ensure the uniformity of the components when mixing powders, and the uneven distribution of inoculants will lead to inconsistent matrix microstructures. Summary of the invention
[0006] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and provide a composition control and preparation method for high-strength and toughness isotropic additively manufactured 316L stainless steel, which is suitable for additive manufacturing technology (such as laser powder bed melting, direct energy deposition, electron beam selective melting, etc.). By optimizing the alloy composition and printing parameters, the microstructure of 316L stainless steel prepared by additive manufacturing technology is improved, and its mechanical properties are improved, providing a basic preparation process support for additive manufacturing of related structural parts in the energy industry.
[0007] The purpose of the present invention can be achieved by the following technical solutions:
[0008] A method for preparing high-strength and toughness isotropic additively manufactured 316L stainless steel comprises the following steps:
[0009] S1: Alloy smelting: According to the element ratio of 316L stainless steel, the raw material composition is controlled by weight percentage and meets the following requirements: C≤0.03wt.%, S≤0.01wt.%, O≤0.06wt.%, N≤0.02wt.%, Cr 16.0-18.0wt.%, Ni 10.0-13.0wt.%, Mn 0.9-1.5wt.%, Mo 2.0-3.0wt.%, Si≤1.0wt.%, and the balance is Fe and unavoidable impurities. Each raw material masterbatch is vacuum smelted at a smelting temperature of 1500-1700°C. As a preferred solution, the smelting temperature is 1600°C and the smelting vacuum degree is ≤5×10 -2 Pa, as a preferred embodiment, the smelting pressure is 5.5Mpa, and an alloy ingot is prepared;
[0010] S2: Gas atomization powder making: The alloy ingots prepared in step S1 are used to prepare 316L stainless steel powder using electrode induction melting gas atomization equipment, and then screened and graded; the gas atomization method is to load the alloy ingots into a leak bag, and the alloy melt flows downward through the leak hole into the gas atomization furnace. Under the action of the inert gas flow, the alloy is crushed into droplets, and finally cooled and solidified into alloy powder.
[0011] The inert atmosphere is an argon atmosphere, and the atomization gas pressure is controlled to be 3-5 MPa.
[0012] After screening, the 316L stainless steel powder is spherical, with a maximum particle size of less than 150 μm, a hollow ball rate of ≤2%, and a sphericity of ≥95%.
[0013] S3: According to the shape and size of the metal parts to be processed, a 3D CAD model of the sample is established using 3D modeling software, and the model information is transmitted to the additive manufacturing equipment;
[0014] S4: The 316L stainless steel powder screened in step S2 is used as raw material, and the process parameters of the additive manufacturing equipment are controlled as follows: laser power 180-220W, scanning speed 750-1250mm / s, layer thickness 0.03-0.05mm, hatch distance 0.08-0.14mm, substrate preheating 80-120°C, argon gas is introduced as a protective gas to deoxygenate the cabin, the oxygen content in the cabin is <0.1%, and an interlayer rotation plus strip scanning strategy is adopted, each layer is rotated 67° between printing, the strip width is 8-12mm, the strip overlap width is 0.08-0.14mm, and printing is performed layer by layer to obtain 316L stainless steel.
[0015] The yield strength of the tensile sample of 316L stainless steel prepared in step S4 perpendicular to the printing direction reaches 400.00-472.92MPa at room temperature, the tensile strength reaches 617.88-691.61MPa, the uniform elongation reaches 37.50-43.33%, and the performance difference between the tensile samples perpendicular to the printing direction and parallel to the printing direction is small, and the difference in ultimate strength, tensile strength and uniform elongation in the two directions is less than 25%.
[0016] The 316L stainless steel obtained in step S4 is equiaxed crystal, and the grain size is 15-23 μm, that is, the method of the present invention realizes the conversion of columnar crystal to equiaxed crystal in the additively manufactured stainless steel material.
[0017] A high-strength and tough isotropic additively manufactured 316L stainless steel prepared by the method has isotropy in microstructure and mechanical properties, realizes the conversion of columnar crystals to equiaxed crystals in the additively manufactured stainless steel material, and refines the grains of the alloy. The yield strength of a tensile sample of the stainless steel material perpendicular to the printing direction at room temperature reaches 400.00-472.92MPa, the tensile strength reaches 617.88-691.61MPa, and the uniform elongation reaches 37.50-43.33%.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] 1. The characteristic indicators of the 316L stainless steel alloy powder for additive manufacturing prepared by the present invention meet the characteristic requirements of the additive manufacturing technology for alloy powder, providing technical support for the industrial preparation of 316L alloy powder.
[0020] 2. In iron-based alloys, the solidification path is changed by adjusting the composition, from the primary austenite mode to the primary ferrite mode, and then phase changes occur during the solidification process and cooling process in the rapid cooling mode, thereby controlling the grain size and grain morphology. In 316L stainless steel, Cr, Mo, and Si are all Cr equivalent elements, and Ni, Mn, C, and N are all Ni equivalent elements. Adjusting the content of related elements to obtain a suitable Cr eq / Ni eq Change the solidification path of the alloy during the rapid cooling process to achieve the transformation from columnar crystals to equiaxed crystals. Specifically, appropriately increase the content of BCC stabilizing elements Cr, Mo, and Si, and reduce the content of FCC stabilizing elements Ni and Mn. Therefore, the 316L stainless steel for additive manufacturing prepared by the present invention, due to the reasonable composition design, plays a role in regulating the microstructure and refining the grains, so that the formed stainless steel sample has isotropic properties, effectively solving the problem of the existence of a large number of columnar crystals in the microstructure parallel to the printing direction of the original additively manufactured stainless steel material, achieving isotropy in performance, and laying a solid foundation for the preparation of uniform microstructure materials by additive manufacturing technology;
[0021] 3. The 316L stainless steel for additive manufacturing prepared by the present invention has good mechanical properties, laying a technical foundation for additive manufacturing of high-strength and tough 316L stainless steel.
[0022] 4. The 316L stainless steel for additive manufacturing prepared by the present invention can be widely used in high-performance structural parts related to the energy industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The microstructure diagram of 316L stainless steel alloy material for additive manufacturing of Example 1 and Comparative Example 2 of the present invention.
[0024] Figure 2 It is a comparison diagram of the engineering stress-engineering strain curves of the 316L stainless steel alloy material for additive manufacturing in Example 1, Example 3 and Comparative Example 2 of the present invention in a direction perpendicular to the printing direction (H) and parallel to the printing direction (V). DETAILED DESCRIPTION
[0025] The following groups of representative embodiments and comparative examples of preparation and mechanical property testing can further illustrate the present invention, but the present invention is not limited to these embodiments. For relevant technical personnel in the field, relevant improvements can be made without departing from the design of the present invention, which all belong to the protection scope of the present invention.
[0026] Unless otherwise specified, all raw materials and equipment used in the present invention are commercially available products.
[0027] Example 1
[0028] A preparation method for additively manufacturing isotropic 316L stainless steel, comprising the following steps:
[0029] S1: Alloy smelting: According to the element ratio of 316L stainless steel in Table 1, each raw material master batch is vacuum smelted at a smelting temperature of 1600° C. and a smelting pressure of 5.5 MPa to prepare an alloy ingot;
[0030] S2: Gas atomization powder making: The alloy ingot obtained in step S1 is used in electrode induction melting gas atomization equipment to obtain 316L stainless steel powder, and then screened and graded; the specific steps are: the alloy ingot is loaded into a leak bag, and the alloy melt flows downward through the leak hole into the gas atomization furnace, and under the action of the inert gas flow, the alloy is crushed into droplets, and finally cooled and solidified into alloy powder. Among them, the atomization gas pressure is controlled to be 3-5MPa.
[0031] After screening, the alloy powder is spherical, with a maximum particle size of less than 150 μm, a hollow ball rate of ≤2%, and a sphericity of ≥95%.
[0032] S3: According to the shape and size of the metal part to be processed, use 3D modeling software (Solidworks software is used in this embodiment) to construct a 55*46*42mm 3 The three-dimensional model of the cuboid is constructed by transmitting the data information of the STL file to an additive manufacturing molding device (in this embodiment, an EOS M290 device produced by EOS GmbH Electro Optical System is selected).
[0033] S4: The 316L stainless steel powder screened in step S2 is used as raw material, and the process parameters of the additive manufacturing equipment are controlled as follows: laser power 189W, scanning speed 928mm / s, layer thickness 0.03mm, hatch distance 0.08mm, laser spot 0.1mm, substrate preheating 80°C, argon gas is introduced as protective gas to reduce oxygen in the cabin, the oxygen content in the cabin is <0.1%, and an interlayer rotation plus strip scanning strategy is adopted. Each layer is rotated 67° between printing, the strip width is 10mm, the strip overlap width is 0.12mm, and printing is performed layer by layer to obtain 316L stainless steel.
[0034] from Figure 1 It can be seen that the average grain size of the additively manufactured 316L stainless steel obtained in Example 1 is 22.35 μm, and the grain morphology in the V direction is equiaxed.
[0035] The obtained 316L stainless steel was made into a plate-like sample with a thickness of 1.5 mm, a gauge width of 2 mm, and a gauge length of 8 mm for tensile testing. The test was carried out using a Zwick Roell Z020 tensile machine with a strain rate of 1×10 -3 / s. The mechanical properties of the tensile sample of the product obtained in Example 1 in the H direction are as follows: tensile strength 617.88MPa, yield strength 400.00MPa, and uniform elongation 39.73%. The mechanical properties of the tensile sample in the V direction are as follows: tensile strength 586.42MPa, yield strength 367.60MPa, and uniform elongation 52.56%; the difference in tensile strength between the H direction and the V direction is 5.09%.
[0036] Example 2
[0037] The raw material formula of this embodiment is shown in Table 1, and the composition is consistent with that of Example 1. The parameters of the printing process are set as follows: laser power 214W, scanning speed 750mm / s, hatch distance 0.12mm, and the rest are the same as in Example 1. The average grain size of the additively manufactured 316L stainless steel obtained is 20.10μm, and the grain morphology in the V direction is equiaxed. The mechanical properties of the tensile sample in the H direction are as follows: tensile strength 624.62MPa, yield strength 398.91MPa, and uniform elongation 42.47%. The mechanical properties of the tensile sample in the V direction are as follows: tensile strength 591.80MPa, yield strength 371.39MPa, uniform elongation 52.79%; the difference in tensile strength between the H direction and the V direction is 5.25%.
[0038] Example 3
[0039] The raw material formula of this embodiment is shown in Table 1. The Mo element content is increased on the basis of Example 1. The parameter settings of the printing process are consistent with those of Example 1. The average grain size of the additively manufactured 316L stainless steel obtained is 18.27μm, and the grain morphology in the V direction is equiaxed. The mechanical properties of the tensile sample in the H direction are as follows: tensile strength 654.79MPa, yield strength 430.41MPa, and uniform elongation 43.33%. The mechanical properties of the tensile sample in the V direction are as follows: tensile strength 635.58MPa, yield strength 439.05MPa, and uniform elongation 51.65%; the difference in tensile strength between the H direction and the V direction is 2.93%.
[0040] Example 4
[0041] The raw material formula of this embodiment is shown in Table 1. On the basis of Example 1, the Si element content is increased and the Mn element content is reduced. The parameter settings of the printing process are consistent with those of Example 1. The average grain size of the additively manufactured 316L stainless steel obtained is 20.10μm, and the grain morphology in the V direction is equiaxed. The mechanical properties of the tensile sample in the H direction are as follows: tensile strength 639.51MPa, yield strength 431.12MPa, and uniform elongation 37.50%. The mechanical properties of the tensile sample in the V direction are as follows: tensile strength 613.87MPa, yield strength 448.11MPa, uniform elongation 49.16%; the difference in tensile strength between the H direction and the V direction is 4.01%.
[0042] Example 5
[0043] The raw material formula of this embodiment is shown in Table 1. The Cr element content is increased on the basis of Example 1. The parameter settings of the printing process are consistent with those of Example 1. The average grain size of the additively manufactured 316L stainless steel obtained is 17.65μm, and the grain morphology in the V direction is equiaxed. The mechanical properties of the tensile sample in the H direction are as follows: tensile strength 687.57MPa, yield strength 466.46MPa, and uniform elongation 41.81%. The mechanical properties of the tensile sample in the V direction are as follows: tensile strength 651.47MPa, yield strength 446.09MPa, and uniform elongation 53.17%; the difference in tensile strength between the H direction and the V direction is 5.25%.
[0044] Comparative Example 1
[0045] The raw material formula of this comparative example is shown in Table 1. The Cr element content is excessively increased on the basis of Example 1. The parameter settings of the printing process are consistent with those of Example 1. The average grain size of the additively manufactured stainless steel obtained is 31.03μm, and the grain morphology in the V direction is columnar crystal. The mechanical properties of the tensile sample in the H direction are as follows: tensile strength 736.52MPa, yield strength 655.52MPa, and uniform elongation 12.44%. The mechanical properties of the tensile sample in the V direction are as follows: tensile strength 689.20MPa, yield strength 671.64MPa, uniform elongation 7.54%; the difference in uniform elongation between the H direction and the V direction is 39.39%.
[0046] Comparative Example 2
[0047] The raw material formula of this comparative example is shown in Table 1, and the Ni content is increased on the basis of Example 1. The parameter setting of the printing process is consistent with that of Example 1.
[0048] from Figure 1 It can be seen that the average grain size of the additively manufactured 316L stainless steel obtained in Comparative Example 2 is 77.02 μm, and the grain morphology in the V direction is columnar crystal.
[0049] The mechanical properties of the tensile samples in the H direction are as follows: tensile strength 577.44MPa, yield strength 434.87MPa, uniform elongation 33.77%. The mechanical properties of the tensile samples in the V direction are as follows: tensile strength 482.88MPa, yield strength 370.17MPa, uniform elongation 69.17%; the difference in uniform elongation between the H direction and the V direction is 51.18%.
[0050] Comparative Example 3
[0051] The raw material formula of this comparative example is shown in Table 1, and the ingredients are consistent with those of Example 1. The parameters of the printing process are set as follows: laser power 164W, scanning speed 485mm / s, hatch distance 0.10mm, and the rest are the same as those of Example 1. A large number of keyholes and cracks appear in the obtained samples.
[0052] Comparative Example 4
[0053] The raw material formula of this comparative example is shown in Table 1, and the ingredients are consistent with those in Example 1. The parameters of the printing process are set as follows: laser power 239W, scanning speed 1250mm / s, hatch distance 0.08mm, and the rest are the same as in Example 1. The rest are the same as in Example 1. A large number of insufficient fusion defects appear in the obtained samples.
[0054] Comparative Example 5
[0055] The raw material formula of this comparative example is shown in Table 1, and the composition is consistent with that of Example 1. The parameter settings of the printing process are consistent with those of Example 1. The molded sample was completely recrystallized in a muffle furnace at 1200°C for 2h. The average grain size of the obtained 316L stainless steel is 25.99μm, and the grain morphology in the V direction is equiaxed. The mechanical properties of the tensile sample in the H direction are as follows: tensile strength 610.97MPa, yield strength 231.02MPa, and uniform elongation 54.71%. The mechanical properties of the tensile sample in the V direction are as follows: tensile strength 580.11MPa, yield strength 298.66MPa, and uniform elongation 64.01%; the difference in tensile strength between the H direction and the V direction is 5.05%.
[0056] Table 1 Alloy components in the present invention (wt.%)
[0057] C S O N Cr Ni Mn Mo Si Fe Example 1 0.002 0.004 0.054 0.009 16.500 10.680 1.270 2.210 0.400 Bal. Example 2 0.002 0.004 0.054 0.009 16.500 10.680 1.270 2.210 0.400 Bal. Example 3 0.014 0.004 0.053 0.006 16.140 10.570 1.410 2.980 0.410 Bal. Example 4 0.021 0.005 0.040 0.011 16.480 10.640 0.990 2.200 0.870 Bal. Example 5 0.026 0.002 0.052 0.006 17.780 10.610 1.410 2.190 0.410 Bal. Comparative Example 1 0.021 0.003 0.060 0.005 19.690 10.670 1.420 2.210 0.410 Bal. Comparative Example 2 0.009 0.003 0.054 0.004 16.320 13.990 1.450 2.240 0.410 Bal. Comparative Example 3 0.002 0.004 0.054 0.009 16.500 10.680 1.270 2.210 0.400 Bal. Comparative Example 4 0.002 0.004 0.054 0.009 16.500 10.680 1.270 2.210 0.400 Bal. Comparative Example 5 0.002 0.004 0.054 0.009 16.500 10.680 1.270 2.210 0.400 Bal.
[0058] Table 2 Comparison of tensile properties of some embodiments of the present invention and comparative examples
[0059]
[0060]
[0061] Table 3 Comparison of grain size between some embodiments of the present invention and comparative examples
[0062]
[0063] In the microstructure of the additively manufactured 316L stainless steel in the embodiment of the present invention parallel to the printing direction, no columnar crystal structure is observed, the columnar crystal is transformed into equiaxed crystal, and no obvious holes and cracks are observed. The density is above 99.9%, and the grain size is less than 23μm. Figure 2 The following is a comparison of the engineering stress-engineering strain curves of the 316L stainless steel alloy material for additive manufacturing in the vertical direction (H) and the parallel direction (V) of the printing direction according to Example 1, Example 3 and Comparative Example 2. The tensile performance test shows that the difference in mechanical properties of the example sample in the H direction and the V direction is smaller than that of the comparative example sample.
[0064] Examples 1 and 2 and Comparative Examples 3 and 4 have the same ingredients, but slightly different printing parameters, mainly focusing on the three parameters of laser power, scanning speed and hatch distance. Examples 1 and 2 are controlled within the scope of the claims of the present invention, the sample density can reach more than 99.9%, and the generation of defects is avoided. However, the scanning speed of Comparative Example 3 is too low, resulting in too high laser energy density input to the molten pool, resulting in keyhole defects. And Comparative Example 4 has too fast scanning speed, resulting in too low energy density input to the molten pool, the metal powder cannot be fully melted, and an incomplete fusion defect occurs.
[0065] Examples 3, 4 and 5 respectively add appropriate amounts of BCC stabilizing elements Mo, Si and Cr on the basis of Example 1, and the contents are within the scope of the claims, thereby increasing the Cr content of the samples. eq / Ni eq , so that the matrix can realize the primary ferrite mode during the solidification process, the sample can complete the transformation from columnar crystals to equiaxed crystals, achieve grain refinement and improve the anisotropy problem in the performance of the original additively manufactured stainless steel.
[0066] In Comparative Example 1, excessive Cr element is added, which exceeds the standard range of 316L, resulting in a large amount of ferrite phase in the final molded sample, which is inconsistent with the austenite matrix of 316L.
[0067] Comparative Example 2 adds Ni element to reduce the Cr eq / Ni eq , so that the matrix realizes the primary austenite mode during the solidification process, the sample can achieve epitaxial growth of grains at the boundary of the molten pool, and a large number of columnar crystals can be observed on the cross section parallel to the printing direction, and the tensile properties Figure 2 This reflects that comparative example 2 has obvious anisotropic behavior in mechanical properties.
[0068] In addition, Comparative Example 4 is a 316L stainless steel sample that has undergone complete recrystallization treatment, and has a microstructure similar to that of the cast 316L stainless steel sample. Its yield strength in the H direction is only 231.02 MPa, which is much lower than 398.91-466.46 MPa in the embodiment. It can be seen that compared with traditional casting technology, additive manufacturing technology has achieved an improvement in the mechanical properties of 316L stainless steel.
[0069] It can be seen that the present invention uses additive technology to achieve the columnar crystal direction equiaxed crystal change of 316L stainless steel parallel to the printing direction (such as Figure 1 ), and can ensure good alloy density, inhibit the generation of holes and cracks, and achieve isotropy in structure and performance (such as Figure 2), and effectively improved the original mechanical properties of the alloy. It has given new power to the application of additive manufacturing stainless steel in the energy industry.
[0070] The above specific description of the embodiments of the present invention is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those familiar with the art can easily make various modifications to these embodiments, and various changes and modifications made within the scope of the claims do not affect the essential content of the present invention. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A composition control and preparation method for high-strength and high-toughness isotropic additive manufacturing 316L stainless steel, characterized in that: The steps include: S1: Alloy smelting: vacuum smelting the raw material master batches according to the element ratio of 316L stainless steel to prepare alloy ingots; the raw material composition of the 316L stainless steel, calculated by weight percentage, meets the following requirements: C≤0.03wt.%, S≤0.01wt.%, O≤0.06wt.%, N≤0.02wt.%, Cr 16.0-18.0wt.%, Ni 10.0-13.0wt.%, Mn0.9-1.5wt.%, Mo 2.0-3.0wt.%, Si≤1.0wt.%, and the balance is Fe and unavoidable impurities; S2: Gas atomization powder making: The alloy ingot obtained in step S1 is used in electrode induction melting gas atomization equipment to make 316L stainless steel powder, which is then sieved and graded; S3: According to the shape and size of the metal parts to be processed, a 3D CAD model of the sample is established using 3D modeling software, and the model information is transmitted to the additive manufacturing equipment; S4: The 316L stainless steel powder screened in step S2 is used as raw material, and the process parameters of the additive manufacturing equipment are controlled as follows: laser power 180-220 W, scanning speed 750-1250 mm / s, layer thickness 0.03-0.05 mm, hatch distance 0.08-0.14 mm, substrate preheating 80°C, and an interlayer rotation plus strip scanning strategy is adopted. Each layer is rotated 67° between printing, the strip width is 8-12 mm, and the strip overlap width is 0.08-0.14 mm. Print layer by layer to obtain 316L stainless steel.
2. The composition control and preparation method of high-strength and toughness isotropic additive manufacturing 316L stainless steel according to claim 1 is characterized in that: The melting temperature of step S1 vacuum melting is 1500-1700°C, and the melting vacuum degree is ≤5×10 -2 Pa.
3. The composition control and preparation method of high-strength and tough isotropic additively manufactured 316L stainless steel according to claim 1, characterized in that: The gas atomization method of step S2 is to load the alloy ingot into a leak bag, and the alloy melt flows downward through the leak hole into the gas atomization furnace. Under the action of the inert gas flow, the alloy is crushed into droplets, and finally cooled and solidified into alloy powder.
4. The composition control and preparation method of high-strength and toughness isotropic additively manufactured 316L stainless steel according to claim 3, characterized in that: The inert atmosphere is an argon atmosphere, and the atomization gas pressure is controlled to be 3-5 MPa.
5. The composition control and preparation method of high-strength and tough isotropic additively manufactured 316L stainless steel according to claim 1, characterized in that: The 316L stainless steel powder obtained in step S2 is spherical, has a maximum particle size of less than 150 μm, a hollow ball rate of ≤2%, and a sphericity of ≥95%.
6. The composition control and preparation method of high-strength and toughness isotropic additively manufactured 316L stainless steel according to claim 1, characterized in that: The yield strength of the tensile sample of 316L stainless steel prepared in step S4 perpendicular to the printing direction reaches 400.00-472.92MPa at room temperature, the tensile strength reaches 617.88-691.61MPa, the uniform elongation reaches 37.50-43.33%, and the performance difference between the tensile samples perpendicular to the printing direction and parallel to the printing direction is small, and the difference in ultimate strength, tensile strength and uniform elongation in the two directions is less than 25%.
7. The composition control and preparation method of high-strength and toughness isotropic additively manufactured 316L stainless steel according to claim 1, characterized in that: The 316L stainless steel obtained in step S4 is equiaxed crystal, and the grain size is 15-23 μm.
Citation Information
Patent Citations
316L stainless steel powder for 3D printing technology and preparation method thereof
CN105537582A
Process for preparing single crystal 316L austenitic stainless steel through selective laser melting
CN115351297A